Analysis of Employee Performance at the Regional Secretariat of the Riau Islands Province During the Covid-19 Pandemic - Lamidi Lamidi (Kemudi, 2022)
Employee performance is a result achieved by employees in their work according to certain criteria that apply to a particular job. Employee performance is a function of the interaction between ability and motivation. The purpose of this paper is to analyze the performance of employees at the Regional Secretariat of the Riau Islands Province during the COVID-19 Pandemic. The research method uses descriptive qualitative. Data collection techniques using secondary data and data analysis using a triangulation approach of relevant facts and logic. The analysis shows that employee performance is not optimal due to the lack of supporting facilities that are not focused on performance budgeting. Because during the COVID-19 period, the focus was only on recovering the national economy so that services at the Provincial Secretariat were not optimal. Then the change in performance culture during the COVID-19 pandemic made employees have to understand information systems and technology in providing public services as a form of service innovation in the future.